International business in times of crisis - Tulder, Rob van; Verbeke, Alain; Piscitello, Lucia; Puck, Jonas (Bingley, U.K. : Emerald Publishing Limited, 2022)
This sixteenth volume in the PIBR series, International Business in Times of Crisis, is dedicated to Professor Geoffrey Jones from the Harvard Business School, and to the importance of historical scholarship in International Business (IB) studies. The global Covid-19 crisis triggered a profound economic crisis, with a decline in global economic activity on a scale not seen since the Great Depression. This pandemic revealed systems failures and fragilities closely related to the organization of global economic, financial, political, and social systems. It has confronted the world with fundamental questions regarding how the global community, as well as companies in general and multinational enterprises (MNEs) in particular, should design global responses to crises. A multi-level and longitudinal approach to studying crises in IB is clearly necessary. This book classifies studies of crises relevant to IB research and will hopefully be helpful to IB scholars, as they reflect on the type of crises they want to study as part of their future research agenda. "The main point coming out of this brief description of my own intellectual journey is to emphasize that crises have been the norm rather than the exception in the history of international business. They have taken many forms and building a typology of crises would be a helpful next step in new research." Geoffrey Jones (in this volume).
Chapter 1. IB in Times of Crisis: What Perspective to Take? / Rob van Tulder, Alain Verbeke, Lucia Piscitello, and Jonas Puck -- Part I. The Longitudinal Perspective - The Importance of Historical IB Studies -- Chapter 2. Crises and International Business / Geoffrey Jones -- Chapter 3. Crises in International Business: A New Perspective / Mark Casson -- Chapter 4. History Matters / Mira Wilkins -- Chapter 5. Crises, Emerging Market Firms, and Global Value Chain Resilience / Pavida Pananond -- Chapter 6. Business Groups, Panics, Runs, Organ Banks and Zombie Firms / Asli M. Colpan and Randall K. Morck -- Chapter 7. Take a Look at Yourself: International Business and the De-globalization Crisis / Michael A. Witt -- Chapter 8. Extraordinary Risk Management in International Business Strategy / Teresa da Silva Lopes -- Part II. The Micro-Perspective - Self-Inflicted Crises -- Chapter 9. How Companies Respond to Self-inflicted Crises. A Comparison Between Countries, Types of Crises, and Response Strategies / Marcus Conrad and Marc Oberhauser -- Chapter 10. Learning Processes During Re-internationalization: A Case Study of Chinese SMEs / Honglan Yu, Margaret Fletcher, and Trevor Buck -- Chapter 11. Switching Governance Modes to Improve the Resilience of Global Value Chains Against External Disruptions / Wenyan Yin and Hwy-Chang Moon -- Part III. Meso-Level Perspective - Sectoral Crises -- Chapter 12. How to Be Smart: Leveraging Digital FDI to Address Risk Through Capacity and Competitiveness / Matthew Stephenson, Lorraine Eden, Michael Kende, Fukunari Kimura, Karl Sauvant, Niraja Srinivasan, Lucia Taioli, and James Zhan -- Chapter 13. COVID-19 Crisis, Digitalization and Location Decisions / Rubina Romanello, and Valerio Veglio -- Chapter 14. Serial Nonlinear Internationalization Before and During the COVID-19 Pandemic: Case Study Evidence From Estonia / Tia Vissak -- Chapter 15. Evolution of Consumption and Retail Transformation - The Emergence of a New Institutional Ord
Includes index.
Print version record.
Keywords: elektronické knihy; electronic books; Crisis management -- Economic aspects; International business enterprises; International economic relations; Business & Economics -- International -- Economics; Economic & financial crises & disasters